Characteristics of porosity properties and wear resistance of aluminum matrix composite (AMC) reinforced with silicon carbide (SiC) particles using stir casting method - A.H Simangunsong; I.K.G. Sugita; D.N.K.P. Negara; I.M. Mara (Dinamika Teknik Mesin, 2026)
The use of composite materials with superior mechanical properties has become an important focus in addressing the challenges of continuously advancing technology, particularly for applications that require lightweight materials with high strength and good corrosion resistance. One material that has attracted considerable interest is aluminum due to its favorable physical, mechanical, and chemical properties. However, aluminum has limitations in terms of hardness and wear resistance, which still need to be improved. This study aims to evaluate the effect of adding silicon carbide particles (SiCp) on the porosity characteristics and wear resistance of aluminum matrix composites (AMC) produced using the stir casting method, which is a technique involving the mixing of molten metal and reinforcement particles through continuous stirring. The casting process was carried out at a temperature of 700 Ã‚Â°C. The variations of SiC composition used were 0%, 1%, 2%, 3%, and 4%. Wear testing was conducted using the reciprocating ball-on-flat method in accordance with the ASTM G133-05 standard, while the porosity level was analyzed through immersion of the samples in a liquid fluid. The results show that an increase in the weight fraction of SiC leads to a reduction in the wear rate, with the lowest wear rate reaching 1.27 Ãƒâ€” 10Ã¢ÂÂ»Ã¢ÂÂ· g/cycle at a 4% SiC fraction and the highest at 0% SiC amounting to 1.84 Ãƒâ€” 10Ã¢ÂÂ»Ã¢ÂÂ¶ g/cycle. In contrast, the porosity calculation shows an increasing trend from 1.85% at 0% SiC to 27.18% at a 4% SiC fraction.